2018
DOI: 10.1111/liv.13887
|View full text |Cite
|
Sign up to set email alerts
|

Serine/threonine protein phosphatase 5 is a potential therapeutic target in cholangiocarcinoma

Abstract: Protein phosphatase 5 negatively regulates AMPK phosphorylation and contributes to CCA aggressiveness; thus, PP5 may be a potential therapeutic target in CCA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…PPP5C plays a crucial regulatory role in multiple signaling pathways through its interactions with various transcription factors and proteins. Dysregulation or abnormal activity of PPP5C is implicated in various diseases, including several cancers, obesity, and Alzheimer's disease [48][49][50][51][52]. Arylalkylamine N-acetyltransferase (AANAT) is a pivotal enzyme in the biosynthesis of melatonin, a crucial regulator of the circadian rhythm, playing a significant role in regulating the circadian clock and influencing various physiological processes, including sleep-wake cycles and seasonal behaviors [53].…”
Section: Discussionmentioning
confidence: 99%
“…PPP5C plays a crucial regulatory role in multiple signaling pathways through its interactions with various transcription factors and proteins. Dysregulation or abnormal activity of PPP5C is implicated in various diseases, including several cancers, obesity, and Alzheimer's disease [48][49][50][51][52]. Arylalkylamine N-acetyltransferase (AANAT) is a pivotal enzyme in the biosynthesis of melatonin, a crucial regulator of the circadian rhythm, playing a significant role in regulating the circadian clock and influencing various physiological processes, including sleep-wake cycles and seasonal behaviors [53].…”
Section: Discussionmentioning
confidence: 99%
“…Research over the last two decades showed that cantharidin and its derivatives can promote tumor regression in multiple cancers via different mechanisms, and numerous analogues were designed to improve efficacy and safety in anti-cancer regimens [12,40]. Targets of cantharidin include protein phosphatases [41][42][43], glutathione S-transferases [44], STAT3 [16,45], Akt [46], and cell division control protein 1 (CDC1) [47]. With focus on the concomitant activation of EGFR and STAT3 as determinants of osteosarcoma progression, we investigated the mechanisms underlying the anticancer effects of SC, a cantharidin analogue, alone and in combination with the EGFR inhibitor erlotinib.…”
Section: Discussionmentioning
confidence: 99%
“…However, its effects on PP1 at the micromolar level (similar to PP2A) and, more importantly, its inhibitory effects on PP5 at the nanomolar level could modulate these reported effects, and their contribution should be clarified [ 20 ]. In fact, PP5 has been demonstrated to play oncogenic functions in cholangiocarcinoma cell lines in vitro and in a xenograft model derived from the human liver bile duct carcinoma cell line HuCCT1 in vivo, at least in part directly binding and regulating AMPK activation [ 21 ]. These considerations are further supported by recent data in the literature demonstrating the opposite functions of PP2A and PP5 in human cancer in the regulation of key pathways such as MAPK signaling [ 22 ].…”
Section: Introductionmentioning
confidence: 99%